The spatiotemporal evolution and spatial effect of digitalization on urban land intensive use in the Yangtze River Economic Belt - Dan Shen; Yuanxiao Hong; Lindong Ma (Humanities & Social Sciences Communications)
Abstract Land is essential for urban development. Increasing land use intensity can help with land shortage, and digitalization has become a new driving force for the development of society. This study uses panel data from 110 cities from 2011 to 2020 in the Yangtze River Economic Belt to empirically verify the impact of digitalization on urban land intensive use (ULIU). Based on analyzing the spatiotemporal evolution of urban digitalization and ULIU, the paper uses four spatial weight matrices and the spatial Durbin model to reveal the impact of urban digitalization on ULIU and discover spatial heterogeneity. We arrive at the following key conclusions: (1) Urban digitalization development is characterized by spatial heterogeneity; The pattern of development shifts from “multi-point” erratic distribution to “cluster” accumulation, and the degree of development in each city differs significantly. The Yangtze River’s downstream cities have become critical high-level digital agglomeration zones. (2) The difference in ULIU level between upstream and downstream of the Yangtze River Economic Belt is more prominent, and the dynamic transfer between tiers is relatively smooth. The correlation between neighboring cities is significant, and the urban spatial agglomeration feature is noticeable (the High-High areas are mainly concentrated in Shanghai, Jiangsu, and Zhejiang). (3) Digitalization can significantly improve ULIU. The adjacency and geospatial effects are pronounced. Spatial heterogeneity is prominent, and cities in the eastern region and within urban agglomerations are subject to a more vital role of digitalization in enhancing ULIU. Finally, based on the findings, this paper proposes to boost ULIU in the Yangtze River Economic Belt.